Crushing Behaviour Of Woven Roving Laminated Conical Shells Using Slipping Solid Cones - Elmabrouk, Bashir Saad (2003)
This project examines experimentally the energy management during the slipping of solid steel cone into composite conical shell. Quasi-static crushing test was carried out with different low speed rate. The cone vertex angles used were 8,1 6, 24, 32 and 40 degrees. The cone height and bottom diameter were kept constant for all cases as 100 mm and 76.2 mm, respectively. Force-stroke curves and deformation histories of typical specimens are presented and discussed. Experimental results show that the cone vertex angle and loading condition affects the load carrying capacity and the energy absorption capability of the conical shell. The axially loaded conical shells between two platens have better load carrying capacity and energy absorption capability compared to the conical shells subjected to slipping. The tearing failure mode is longitudinal fibres and occurs near the contact area between the solid steel cone and the conical shell wall (out-of-plane tearing mode). Furthermore, the structure subjected to plated test crushed at the small end in splaying failure-crushing mode. Based on experimental results obtained from this investigation, it could be concluded that at first-crush stage the energy is dissipated in the form of friction and the conical shell responded to slipping force in an elastic manner, while the post crush stage is dominated by the tensile tearing failure foll owed by longitudinal and transverse shear cracking failure. The developed FORTRAN computer program approximately predicts the initial failure load. The discrepancy between the analytical solution prediction and the experimental results is due to the assumption made in FORTRAN computer program.